PENGARUH PROFESIONALISME DAN DUKUNGAN MANAJERIAL TERHADAP KINERJA KARYAWAN DENGAN KOMITMEN ORGANISASI SEBAGAI VARIABEL INTERVENING PADA PT PLN NUSA DAYA DI KABUPATEN MIMIKA - Andreas Falentino Ayer; Muhammad Fadhli; Abu Bakar (Adisam Publisher, 2025)
This study aims to analyze the influence of professionalism and managerial support on employee performance, with organizational commitment as an intervening variable at PT PLN Nusa Daya in Mimika Regency. A quantitative approach using an associative method was applied, and data were collected through questionnaires from 48 employees as the sample. Data analysis was conducted using Structural Equation Modeling (SEM) with Partial Least Squares (PLS) through SmartPLS 4 software. The results showed that professionalism and managerial support have a positive and significant direct effect on employee performance. Furthermore, both independent variables significantly affect organizational commitment, which in turn positively influences employee performance. Organizational commitment was proven to significantly mediate the indirect effect of professionalism and managerial support on employee performance. The practical implications of this study emphasize the importance of developing professionalism, enhancing managerial support, and strengthening organizational commitment to improve employee performance, particularly in challenging work environments such as PT PLN Nusa Daya.